Підвищення енергоефективності електросталеплавильних процесів шляхом конверсії природного газу з відпрацьованими газами дугової печі - Gubinskii M.V.; Timoshenko S.N.; Shraiber; Antonets I.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2017)
We have developed a new scheme of the electric steelmaking process with thermochemical recuperation, i.e., natural gas conversion with the exhaust gases of an arc furnace for scrap preheating. Thermodynamic calculations show that this scheme provides an increase in the thermal efficiency of the furnace by 5–6%, fuel economy by 21%, and a decrease in CO2 emission to the atmosphere by 9.8%.